Information systems freshmen teaching: Case experience from day one - Nicolas Pflanzl; Katrin Bergener; Armin Stein; Gottfried Vossen (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2014)
[Introduction ...] The remainder of this paper is organized as follows: Section 2 covers background material on IS courses in general and the one at Münster in particular. Section 3 describes the design of our course in detail, while Section 4 provides a discussion of the approach both from a teacher's and from a student's perspective. Finally, Section 5 presents our conclusions as well as a brief outlook.
Keywords: 650